2021
DOI: 10.3389/fpsyg.2021.671553
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-Being in Chinese College Students During the COVID-19 Pandemic: Roles of Resilience and Environmental Stress

Abstract: Psychological well-being is an important indicator of well-being and has been found to be associated with a multitude of positive life outcomes. Using data collected from 1,871 Chinese college students from September 23 to October 5, 2020, this study examined students' psychological well-being during the COVID-19 pandemic and investigated how resilience and pandemic-related environmental stress may affect psychological well-being. Results showed that resilience had strong positive effects on psychological well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 52 publications
(87 reference statements)
6
46
0
1
Order By: Relevance
“…Resilience is the ability to rise from adversity [12]. In the educational context, studies have shown that resilience affects students' psychological well-being and positive behaviors during the COVID-19 pandemic [12][13][14][15]. Therefore, in this study, resilience, a variable studied in positive psychology, is set as a moderated mediation variable, as research shows that students with strong resilience tend to cope with stressful situations more actively.…”
Section: Introductionmentioning
confidence: 98%
“…Resilience is the ability to rise from adversity [12]. In the educational context, studies have shown that resilience affects students' psychological well-being and positive behaviors during the COVID-19 pandemic [12][13][14][15]. Therefore, in this study, resilience, a variable studied in positive psychology, is set as a moderated mediation variable, as research shows that students with strong resilience tend to cope with stressful situations more actively.…”
Section: Introductionmentioning
confidence: 98%
“…A study in China found a positive relationship between academic self-efficacy and student well-being ( Yang et al, 2021 ). In addition, in September 2020, another study found that university students reported good psychological well-being when some of the preventive measures were lifted by April 2020, such as the return to classes at some universities ( Tan et al, 2021 ). Emotional self-efficacy has also been found to be negatively associated with fear of contagion in Italian university students.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the immediacy of the event, very few empirical studies have been carried out (or published to date) on this period of time. Among them, we can mention the study of Tan et al [28], who, with a sample of 1871 Chinese college students, found that resilience had a strong positive relationship with psychological well-being during the pandemic. Paredes et al [18] showed that the relationship between the perceived threat of COVID-19 and psychological well-being is mediated by resilience.…”
Section: Resiliencementioning
confidence: 99%